Hidden zeros in exceptional field theories from double copy - Yang Li; Diederik Roest; Tonnis ter Veldhuis (Journal of High Energy Physics)
Abstract It was recently discovered by Arkani-Hamed et al. and Cao et al. that the colour-ordered scattering amplitudes of Tr(Φ3), the non-linear sigma model and Yang-Mills-scalar vanish at specific loci. We build on this observation and demonstrate that, beyond colour ordering, scattering amplitudes can display higher-order hidden zeros. A first example are the flavour-paired amplitudes of gravity-coupled scalars, as a double copy of Yang-Mills-scalar. The other two cases are Dirac-Born-Infeld and the special Galileon, which are the natural generalisations of the non-linear sigma model with higher orders of the Adler zero. We demonstrate that the amplitudes of these theories all factorize into lower-point objects in the near-zero limit, and discuss their interpretation. Finally, we comment on the general picture of hidden zeros and prove their relation under the double copy.